2016
DOI: 10.1080/13504630.2016.1244766
|View full text |Cite
|
Sign up to set email alerts
|

Biographies and the doubleness of inclusion and exclusion

Abstract: Integration is often considered to be comprised of different dimensions which can influence each other in a linear fashion. For instance, if one becomes more proficient in the host country's language, one's labor market participation should also increase. In the Netherlands, this assumption has led to a plethora of policies (like mandatory integration courses) having targeted especially 'Muslim' women of Moroccan and Turkish descent, who are perceived as most isolated in society. Obliging them to learn Dutch w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 23 publications
(27 reference statements)
1
12
0
Order By: Relevance
“…There are many similarities in the paradoxes (of language and socioeconomic integration) present in the narratives of this research with those found in other studies on various generations of migrants and refugees with Islamic backgrounds (e.g., Eijberts & Ghorashi, 2016). We hope, with the results of this study, to weaken the "culturalist" foundation of the present discourse on integration.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…There are many similarities in the paradoxes (of language and socioeconomic integration) present in the narratives of this research with those found in other studies on various generations of migrants and refugees with Islamic backgrounds (e.g., Eijberts & Ghorashi, 2016). We hope, with the results of this study, to weaken the "culturalist" foundation of the present discourse on integration.…”
Section: Discussionsupporting
confidence: 62%
“…For the second-wave migrants, we found that those who had succeeded in learning fluent Dutch, who worked, and could be considered successfully integrated, as defined by Esser's (2003) first three dimensions of integration, indicated that they felt neither Dutch nor at home in the Netherlands. Knowledge of the Dutch language and active participation in the workforce led to exposure to the exclusionary aspects of not being Dutch, which had a negative impact on their sense of belonging (see also Eijberts & Ghorashi, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Home captures both material and immaterial aspects. The material aspects are associated with physical, tangible and visible elements such as furniture and food (Buitelaar and Stock, 2010; Duruz, 2010), whereas the immaterial aspects are associated with intangible, emotional and social elements such as language and culture (Eijberts and Ghorashi, 2016; Kusenbach and Paulsen, 2013: 8–9). Elements of home also include material (object-centred) and immaterial (people- or relational-centred) characteristics, and all of these elements help make up the functions of one’s home.…”
Section: Home In Theoretical Perspectivementioning
confidence: 99%
“…That is, while civic integration is predicated on ‘inclusion’ through ‘respecting diversity’ it can also exclude by ‘problematising integration deficits’ (Duemmler, 2015: 393). Similarly, Eijberts and Ghorashi (2017) highlight how ‘integration strategies might have both positive and paradoxically negative effects at the same time, by heightening a sense of inclusion and exclusion, belonging and non-belonging’ (p. 165).…”
Section: Parallax Conviviality and Transiting Past And Presentmentioning
confidence: 99%